2019
DOI: 10.3389/fpubh.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

Development, Implementation, and Process Evaluation of a Theory-Based Nutrition Education Programme for Adults Living With HIV in Abeokuta, Nigeria

Abstract: Introduction: Healthy diets play a role in the management and care for adults living with HIV/AIDS (ALH). Appropriate nutrition education (NE) is necessary to equip ALH with relevant knowledge and skills for healthy eating. A needs assessment identified the need for a nutrition education programme (NEP) as part of the nutrition service for ALH in Abeokuta, Nigeria. The aim of this study was to design a theory-based NEP and to evaluate the implementation process among ALH attending selected federal and state ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…The follow-up sessions, number and duration of nutrition education and physical activity sessions, and vitamin or mineral supplementation did not go on as had been planned. In disagreement of current study, the process evaluation of two studies in Nigeria and USA has shown the delivery rate of 100% (42,43). Several factors may have contributed to low level of delivery in current study; most of the providers reported that they had not enough time to dedicate on EINCP as they had other tasks in the health care centers.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The follow-up sessions, number and duration of nutrition education and physical activity sessions, and vitamin or mineral supplementation did not go on as had been planned. In disagreement of current study, the process evaluation of two studies in Nigeria and USA has shown the delivery rate of 100% (42,43). Several factors may have contributed to low level of delivery in current study; most of the providers reported that they had not enough time to dedicate on EINCP as they had other tasks in the health care centers.…”
Section: Discussionmentioning
confidence: 53%
“…77.5% of the clients had exposure to the program. Clients' satisfaction rate was varied from 4.2 to 34.7% with various available services, but 42.8% of the clients had high satisfaction with overall parts of the EINCP. The program also suffered from some external contexts such as the lack of financial support of program providers.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to the current study, process evaluations in Nigeria and the US have shown a delivery rate of 100%. 30,31 In the current study, several factors may have contributed to the low level of delivery, including insufficient time on the part of the providers and lack of attention to providers' specialties. It is speculated that poor delivery of the program components might have resulted in diminished EINCP effects, as confirmed by another study.…”
Section: Discussionmentioning
confidence: 82%
“…Approximately 1400 ALH at each hospital received free ART which they collected on a monthly basis. A needs assessment, conducted prior to the current study to determine the NE needs of the ALH at the two hospitals, showed the ALH attending the two hospitals to have similar demographic and anthropometric characteristics ( P > 0·05) ( 17 ) .…”
Section: Methodsmentioning
confidence: 94%
“…Convenience sampling was used to recruit 200 ALH who met the inclusion criteria and consented to participate in the study. The sample size was determined from the results of the prior needs assessment ( 17 ) where 169 of the 243 participants answered all the Short Form (SF)-36 QoL questions with a mean of 65 ( sd 14·7) %.…”
Section: Methodsmentioning
confidence: 99%